2020
DOI: 10.3390/jcm9061795
|View full text |Cite
|
Sign up to set email alerts
|

Differential Th Cell-Related Immune Responses in Young Physically Active Men after an Endurance Effort

Abstract: The participation of T cell subsets in the modulation of immunity in athletes triggered by maximal effort was investigated. In total, 80 physically active young men (range 16–20 years) were divided into 5 age groups: 16, 17, 18, 19, and 20 years old. They performed efficiency tests on mechanical treadmills until exhaustion. White blood cell (WBC) and lymphocyte (LYM) counts were determined, and the type 1 (Th1), type 2 (Th2) helper T cells, T helper 17 (Th17), and T regulatory (Treg) cell distribution and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 54 publications
8
21
1
Order By: Relevance
“…If leukocytopenia, including lymphocytopenia manifested after a soccer match, the recovery period compensated for it since it was not observed in our study. Similarly, in our previous study no leukocyto- and lymphocytopenia was found 17 h after a maximal exercise bout among professional soccer players 32 and physically active young men 44 . Although previous studies suggest that neutrophils are mobilized in response to exercise-induced muscle damage 5 , 24 , we did not observe significant changes in total WBC counts or in granulocyte distribution in subjects after post-match recovery.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…If leukocytopenia, including lymphocytopenia manifested after a soccer match, the recovery period compensated for it since it was not observed in our study. Similarly, in our previous study no leukocyto- and lymphocytopenia was found 17 h after a maximal exercise bout among professional soccer players 32 and physically active young men 44 . Although previous studies suggest that neutrophils are mobilized in response to exercise-induced muscle damage 5 , 24 , we did not observe significant changes in total WBC counts or in granulocyte distribution in subjects after post-match recovery.…”
Section: Discussionsupporting
confidence: 72%
“…Simpson postulated that the number of lymphocytes usually reaches a resting value in the peripheral blood up to 24 h after exercise 47 . However, our previous studies showed that the peripheral blood lymphocyte distribution in young, physically active men 17 h after progressive effort 32 , 44 significantly differed from pre-exercise values. Navalta et al also showed changes in the distribution of Th and Tc cells following 3-day, high-intensity interval exercises, which resulted from pro-apoptotic pathway activation and lymphocyte migration from lymphoid tissues to the peripheral blood 28 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The participants were general morphologically and physiologically characterized before the study according to a protocol described previously [25] and the parameters are presented in Table 1. The body mass, body mass index (BMI), basal metabolic rate (BMR), percentage of fat (FAT), fat mass (FAT MASS), and total body water (TBW) were determined using a Body Composition Analyzer (Tanita BC-418MA, Tokyo, Japan).…”
Section: The Participants' Characteristicmentioning
confidence: 99%
“…This is an important mechanism of regulation of general inflammation induced by various biological factors. The role of Th and Treg cell subsets in modulation of the immune response to endurance effort is well described [22][23][24][25][26]. It is also known that T lymphocyte metabolism is directly controlled by signaling pathways responsible for the activity of these cells and their survival in response to stress stimuli [27].…”
Section: Introductionmentioning
confidence: 99%